Gas separation performance of polyethersulfone/multi-walled carbon nanotubes mixed matrix membranes - Ismail, Ahmad Fauzi (Pergamon Press, 2011)
Mixed matrix membranes (MMM) comprised of multi-walled carbon nanotubes (MWCNTs) inside polyethersulfone (PES) matrix were fabricated and characterized for gas separation performance. The MWCNTs were purified with acid mixtures (HNO3/H2SO4; v/v = 1:3) to remove carbonaceous impurities followed by surface functionalization with 3-aminopropyltriethoxylsilane (APTES) to allow well dispersion of the tubes in organic solvent such as N-methlypyrrolidone (NMP) during the preparation of PES/MWCNTs suspension. Effects of purification, functionalization and MWCNTs loading on the gas permeation properties of the MMM were investigated by varying the MWCNTs loading in the PES matrix from 0.5–3.0 wt.%. The fabricated MWCNTs/PES MMM were characterized by scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetry analysis (TGA) and pure gas permeation test. Gas permeation measurement showed that MMMs embedded with different kinds of applied CNTs exhibited different separation performances. For example, gas permeation measurement showed that MMM embedded with 1.0 wt.% purified and functionalized MWCNTs possessed better performances in terms of permeability and selectivity in comparison to raw MWCNTs. The highest gas selectivity was achieved at 0.5 wt.% MWCNTs loadings (aCO2/CH4 = 250.13; aO2/N2 = 10.65) and decreased as the loadings were increased from 1.0 to 3.0 wt.%. The reduction in performance possibly due to the presence of interface voids which became prominent at higher MWCNTs loading. The high selectivity of fabricated MMM suggested that the present works have a great potential to be utilized practically in gas separation technology.